Phase-Coherent Optical Frequency Up-Conversion with Millimeter-Size Zn(3-Ptz)2 Metal-Organic Framework Single Crystals - Herrera-Urbina, F; Singh, D; Enríquez-Montenegro, J; Fritz, R; Garcia-Garfido, J (John Wiley and Sons Inc, 2023)
Metal-organic frameworks (MOFs) have emerged as candidate materials for nonlinear optics due to their enhanced optical and chemical stability in comparison with conventional organic crystals. However, producing large single crystals that support perfect phase matching conditions for frequency conversion is a long-standing challenge due to the highly metastable conditions in which MOF crystals tend to self-assemble in solution. By modulating the synthesis and growth conditions, this limitation is overcome to produce millimeter–sized Zn(3-ptz)2 uniaxial MOF single crystals. Optimized MOF crystals with large birefringence in the visible Δn ≈ −0.3 and high transparency allow for the observation of strong second-harmonic (SHG) and third-harmonic generation (THG) signals for the first time, using femtosecond near-infrared pump pulses. For conditions of type-I SHG phase-matching, the measured effective nonlinear coefficient of Zn(3-ptz)2 is deff ≈ 0.10 pm V−1, the largest measured nonlinearity for MOF materials to date. The experiments quantitatively agree with first-principles simulations based on the crystal lattice structure. The damage threshold is estimated on the order of 0.2 TW cm−2 for raw single crystals, which can be further increased with additional crystal engineering steps. The demonstration of efficient frequency up-conversion of light with long-range phase coherence establishes MOF single crystals as promising materials for nonlinear optical devices. © 2023 The Authors. Advanced Optical Materials published by Wiley-VCH GmbH.